The Association of Epidemiological and Clinical Parameters with Diabetes and Hypertension in a Rural Area: A Mahbubnagar District Study - Munnaji Vyankatesh Mavatkar; Kiran Prakash Kanaparthi; Aruna Devi Sadamalla; Arif Mahboob Syed; Yamini Anjaneya Rao Vaia (Masters Program in Public Health, 2022)
Background: Rapid development in a country like India has also brought an explosion in the prevalence of non-communicable disease. Affluence to western culture can be one of the reason. This might have encroached the rural India. A cross‑sectional survey was done to assess the socio-demographic, clinical and laboratory factors diabetes and hypertension among the study population.Subjects dan Method: This is a descriptive cross-sectional study. A sample of 244 diabetes and hypertensive patients registered under the subcentre were taken as study subjects. Sociodemographic factor, clinical parameters and Laboratory parameters were taken independent variables. The dependent variables were diabetes and hypertension. Data analysis was done with help of SPSS version 26 software. Standard instruments were used to measure, weight, height, and waist circumference (WC), blood pressure. The random blood sugar, HbA1C and lipid profile values were taken from laboratory reports. The other variables were collected by questionnaire.Results: A total of 244 participants reported and responded to this study who were having diabetes, hypertension or both. About 35% of the population belonged to lower SEC. Amongst males almost 50% of the male had dual co-morbidity i.e Diabetes and Hypertension. About 85% of the population was Illiterate (p<0.05). Mean value of HbA1C was high among the diabetic patient who were under treatment (Mean= 7.10; SD=1.20). Lipid profile value were in normal range but higher compared to stats of other selected states.Conclusion: Study subjects even on treatment were unable to keep the laboratory parameters under control hence requiring indepth research. Keywords: Diabetes, hypertension, risk factors, Mahbubnagar District. Correspondence:Munnaji Vyankatesh Mavatkar. Assistant Professor Department of Community Medicine Government Medical College Mahbubnagar. Department of Community Medicine Government Medical College Mahbubnagar Yedira 509001. Email: Kiranmavatkar0647@gmail.com. Mobile phone: 08999712782.